2020
DOI: 10.1042/bcj20200311
|View full text |Cite
|
Sign up to set email alerts
|

An acidic residue buried in the dimer interface of isocitrate dehydrogenase 1 (IDH1) helps regulate catalysis and pH sensitivity

Abstract: Isocitrate dehydrogenase 1 (IDH1) catalyzes the reversible NADP+-dependent conversion of isocitrate to α-ketoglutarate (αKG) to provide critical cytosolic substrates and drive NADPH-dependent reactions like lipid biosynthesis and glutathione regeneration. In biochemical studies, the forward reaction is studied at neutral pH, while the reverse reaction is typically characterized in more acidic buffers. This led us to question whether IDH1 catalysis is pH-regulated, which would have functional implications under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 114 publications
1
10
2
Order By: Relevance
“…These structural data are supported by our prior collaborative work using computational analyses to identify a pH sensitive network of ionizable residues at the homodimerization interface of WT IDH1. 14 Our heterodimer data suggest that maintaining this hydrogen bond network via a positively charged Arg interacting with a negatively charged Asp is important for dimerization. Indeed, the increased heterodimer formation we observe specifically at low pHi, where His132 is more likely to be protonated, supports this hypothesis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These structural data are supported by our prior collaborative work using computational analyses to identify a pH sensitive network of ionizable residues at the homodimerization interface of WT IDH1. 14 Our heterodimer data suggest that maintaining this hydrogen bond network via a positively charged Arg interacting with a negatively charged Asp is important for dimerization. Indeed, the increased heterodimer formation we observe specifically at low pHi, where His132 is more likely to be protonated, supports this hypothesis.…”
Section: Discussionmentioning
confidence: 75%
“… 13 Prior work suggests that WT IDH1 reactions could be sensitive to environment or microenvironment changes, with low buffer pH enhancing the reverse reaction (AKG → ICT) 13 and high buffer pH enhancing the forward reaction (ICT → AKG) in vitro . 14 These in vitro results with recombinant enzyme have some dependence on the specific buffer systems used, and the most pronounced effects require pH values outside the physiological range (7.0–7.6). However, this work does suggest that IDH1 function may be linked to environmental cues.…”
mentioning
confidence: 99%
“…Recently, we described a mechanism of pH regulation of WT IDH1 catalysis, a long-described phenomenon whose mechanism was not well understood. We found that the catalytic rate of the forward reaction (isocitrate to αKG) was increased upon increasing pH [ 102 ]. To establish the mechanism of pH sensitivity, we identified a buried aspartic acid residue in WT IDH1, D273, that sensed local changes in pH likely by undergoing a change in protonation state ( Figure 2 ) [ 102 ].…”
Section: Role Of the Cellular Environment In Modulating Enzyme Activi...mentioning
confidence: 99%
“…of isocitrate to 2OG and CO 2 , is usually studied at neutral pH, with the reverse reductive decarboxylation reaction being preferred at acidic pH [ 19 ]. The k cat for wtIDH catalysed isocitrate oxidation increases from 20.0 ± 0.4 s −1 to 38.3 ± 0.9 s −1 as the pH increases from pH 6.2 to pH 8 with maximal efficiency about pH 7.5, (1.4 ± 0.1) × 10 3 mM − 1 s − 1 [ 92 ]. These observations suggest that cellular pH may influence wtIDH/IDH variant catalysis.…”
Section: Idh Wild-type and Variant Enzyme Kineticsmentioning
confidence: 99%
“…Modulation of the ionisation state of Asp273 is proposed to be involved in the pH-mediated regulation of wtIDH; substitutions of Asp273 reduce catalytic efficiency and cause loss of pH regulatory effects [ 92 ]. The intracellular pH (pHi) has been measured as 7.01 ± 0.2 in normal brain in vivo by 31 P Magnetic resonance spectroscopy (MRS) but is more basic (pHi 7.18) in glioma [ 32 , 93 ].…”
Section: Idh Wild-type and Variant Enzyme Kineticsmentioning
confidence: 99%